Diversidade microbiana em açude de uma região semiárida do Nordeste brasileiro: uma perspectiva de integração entre a ciência do laboratório e a ciência da sala de aula - Peixe, Paula Dorti (2017)
The sustainable use of natural resources has been a concern of the 21st century. Among them, water stands out as it guarantees the permanence of life on the planet, with emphasis on the communities of microorganisms, responsible for exercising an important ecological role, which is reason for its study. It is important to emphasize that the accumulated knowledge on this topic needs to be reflected as an unfolding in the area of science teaching. Thus, this study aimed to identify the microbial biodiversity, especially the bacterioplankton, of a reservoir in the northeastern semiarid region, thus contributing to the understanding of the composition and ecological dynamics played by the microbiota. In addition, biological textbooks on DNA and Biotechnology were analyzed in order to identify if they deal with these contents in a perspective that relates the conceptual theory to the social and environmental context, that is, if there is a teaching perspective based on the relations between Science, Technology and Society (CTS), as well as to identify the didactic strategies of Biology teachers to teach these subjects in public schools in the semi-arid region of Rio Grande do Norte. In order to promote the facilitation of knowledge and teaching of genetics (DNA and Biotechnology), a teacher training course on recombinant DNA technology was offered using a variety of teaching strategies. The obtained results demonstrated, through molecular techniques, that the weed had the predominance of the Domain Bacteria - Phylum Cyanobacteria, Proteobacteria, Actinobacteria. Virus and Archaea were also found. Despite the importance of the CTS approach to Biology Teaching, most textbooks did not demonstrate a relation of scientific and technological knowledge with a direct implication for society and the environment. It was also found that 73% of teachers present difficulties in teaching topics related to DNA and Biotechnology and 100% of them stated that students also have difficulty understanding this content. In addition, 58% of the members of the teacher training course understand its importance, since they perceived several possibilities for the enrichment of science and biology classes, showing their importance for the contribution of the teaching practice and approximately 33% of the teachers reported That the theme developed presents constant innovation, which implies the need for them to have greater contact with scientific development to keep themselves informed and, consequently, apt to teach it in the classroom. It is concluded that of the analyzed microbiota, the predominance of the phylum Cyanobacteria, can be indicative of eutrophic environment, as mentioned by previous studies carried out in the same area of study. In addition, it was only with the advent of molecular techniques that it was possible to identify some bacterial phyla, such as Actinobacteria, common in freshwater habitats. It was concluded that the CTS approach in the textbook is still fragile in the textbooks evaluated in this study. It can generate a consequent discouragement, as it is not linked to the social context of the student. With regard to the training courses, it is concluded that they are extremely important because they allow teachers the opportunity to keep up-to-date, both in terms of specific content and pedagogical strategies for facilitating teaching and learning. In general, this research integrated the empirical knowledge of the use of molecular techniques for the identification of microbiota with the development in the area of science education, based on the assumption that a robust scientific education contributes to the environmental preservation, in this case in particular, of Aquatic environments. Since the dominant model of education is still the traditional one, it is important to highlight the importance of continuing education courses in this study.